2000
DOI: 10.1209/epl/i2000-00421-1
|View full text |Cite
|
Sign up to set email alerts
|

AFM study of surface roughening in sputter-deposited nickel films on ITO glasses

Abstract: We have studied the kinetic surface roughening of nickel films sputter-deposited on ITO glasses within a temperature range from 423 K to 573 K. The scaling exponents were determined by the surface measurements of AFM and compared with theoretical values in the surface diffusion-driven growth model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…[35][36][37][38][39][40][41] In our case, for instance, ␤ is equal to 0.67. This behavior is shared by many of the surface growth systems displaying anomalous scaling.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…[35][36][37][38][39][40][41] In our case, for instance, ␤ is equal to 0.67. This behavior is shared by many of the surface growth systems displaying anomalous scaling.…”
Section: Discussionmentioning
confidence: 68%
“…44 These facts indicate that shadowing effects could play an important role in the film dynamics as other authors have already suggested. 16,36,41 Shadowing effects also imply that regions located at higher surface positions ͑peaks or protrusions͒ grow faster at the expense of others ͑valleys͒, which is known to lead to unstable growth morphologies with large ␤ values, 45 analogous to the diffusional instabilities found in electrodeposition. 17,29 Available models of shadowing in 2 + 1 dimensions predict 1 / z =1/3 and ␤ =1.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, many of the scaling studies of the films deposited by sputtering share this behavior, as they display ␤ values ranging from 0.4 up to 0.8. These values are mainly found for polycrystalline systems 17,18,[32][33][34][35] and also for amorphous silicon. 19 Finally, for sputtered deposition of platinum on glass, with simultaneous substrate rotation, it was found that the growth dynamics is governed by linear diffusion.…”
Section: Discussionmentioning
confidence: 88%
“…39 These facts indicate that shadowing effects could play an important role in the film growth dynamics as other authors have already suggested. 16,18,19 Shadowing effects imply a scenario in which one type of region, usually those located at higher surface positions ͑"bumps"͒, grows faster at the expense of others ͑"valleys"͒, which is known to lead to unstable growth morphologies with large ␤ values. 40 Models of shadowing in 2 + 1 dimensions predict 1 / z =1/3 and ␤ =1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation